Unified Approach to the Treatment of Hypertrophic and Atrophic Scars: A Pilot Study. (December 2016) - Chambers, Alexandra
Hypertrophic and atrophic scars are typically thought to be at opposite ends of the pathological healing process, and, as a consequence, cosmetic treatments have tended to be varied and disparate. This article, however, presents data from a pilot study that illustrates a coherent and unified approach can be used for the effective treatment of both scar types. This method studies the use of a precision microneedling device using mixed length needles. This is used in conjunction with the application of topical, pharmaceutical-grade creams consisting of retinoic acid, antioxidants, anti-inflammatory agents, and sea sponge collagen. Data and examples are presented that show good skin remodeling for both types of scars.